Tunisia : Report on the Observance of Standards and Codes. (IMF Staff Country Reports; Country Report ;, 2002)
This report evaluates the Observance of Standards and Codes on data dissemination, fiscal transparency, the transparency of monetary policy, banking supervision, and securities market regulation for Tunisia. The assessment reveals that Tunisia has already achieved a considerable degree of transparency in fiscal management. Further improvements in data preparation and dissemination have come about recently during the process of subscribing to the Special Data Dissemination Standards. In addition, the implementation of the new tax code (code des procedures fiscales) has further clarified the rights and obligations of taxpayers and the government on matters relating to taxation.